Genomic Analysis Reveals Genetic Distinctiveness of the Paiute Cutthroat Trout Oncorhynchus clarkii seleniris. Issue 6 (24th July 2017) - Saglam, Ismail K.; Prince, Daniel J.; Meek, Mariah; Ali, Omar A.; Miller, Michael R.; Peacock, Mary; Neville, Helen; Goodbla, Alisha; Mellison, Chad; Somer, William; May, Bernie; Finger, Amanda J.
Abstract: The Paiute Cutthroat Trout (PCT) Oncorhynchus clarkii seleniris is classified as a subspecies within the greater Cutthroat Trout O. clarkii ssp. complex and is federally listed as threatened under the Endangered Species Act. However, genetic studies to date have revealed very little genetic differentiation between the PCT and its closest relative, the Lahontan Cutthroat Trout (LCT) O. clarkii henshawi . These results casted doubt on whether the PCT is a genetically distinct subspecies or merely a phenotypic variant of the LCT. Here, we present a genomic analysis of Cutthroat Trout subspecies and populations to resolve the genetic and phylogenetic relationship between PCT and LCT. Our results demonstrate substantial genetic structure and differentiation between PCT and LCT populations. In contrast to current thinking, our phylogenetic reconstructions show the PCT to be a distinct evolutionary lineage that diverged from LCT before the LCT differentiated into its current populations (i.e., rather than PCT divergence due to geographic isolation from an LCT population in the Carson River). We conclude that the PCT is genetically distinct from the LCT.